Are credit default swaps associated with higher corporate defaults? - Stavros Peristiani; Vanessa Savino (Federal Reserve Bank of New York, 2011)
Are companies with traded credit default swap (CDS) positions on their debt more likely to default? Using a proportional hazard model of bankruptcy and Merton's contingent claims approach, we estimate the probability of default for US nonfinancial firms. Our analysis does not generally find a persistent link between CDS and default over the entire period 2001-08, but does reveal a higher probability of default for firms with CDS over the last few years of that period. Further, we find that firms trading in the CDS market exhibited a higher Moody's KMV expected default frequency during 2004-08. These findings are consistent with those of Henry Hu and Bernard Black, who argue that agency conflicts between hedged creditors and debtors would increase the likelihood of corporate default. In addition, our paper highlights other explanations for the higher defaults of CDS firms. Consistent with fire-sale spiral theories, we find a positive link between institutional ownership exposure and corporate distress, with CDS firms facing stronger selling pressures during the recent financial turmoil.
Keywords: G21; G33; 330; credit derivatives; corporate bankruptcy; Merton's distance to default